PENGARUH AUDIT FEE, JASA NON AUDIT, UKURAN KAP DAN LAMA HUBUNGAN AUDIT TERHADAP INDEPENDENSI PENAMPILAN - Devy Paramastri, I.D.A.A.; Dharma Suputra, I.D.G. (E-Jurnal Akuntansi, 2016)
The independence of an appearance of independence is determined by impressions, opinions against the independence of public accountants individually and as a whole. The purpose of this study was to examine the effect of audit fees, non-audit services, the size of the firm, long relationship with the audit client to the independence of appearance accountant. The Methods of sampling is purposive sampling, with sample of 60 people. The analysis technique used is multiple linear regressions and classical assumption. Results of this research is the audit fee, the size of the firm and long-standing relationships with the audit client's positive effect on the independence of public accountants appearance while non-audit services negatively affect the appearance of the independence of public accountants.
Keywords: Audit Fee, Size KAP, Non Audit Services, Long Relationship Audit and Independence of Appearance